Measurement of Source Star Colors with the K2C9-CFHT Multi-color Microlensing Survey - Zang, Weicheng; Penny, Matthew T.; Zhu, Wei; Mao, Shude; Fouqué, Pascal; Udalski, Andrzej; Hwang, Kyu-Ha; Wang, Tianshu; Huang, Chelsea; Boyajian, Tabetha. S.; Barentsen, Geert (Publications of the Astronomical Society of the Pacific, 2018)
Microlensing events observed from locations separated by ∼au have different peak times and peak magnifications due to microlensing parallax. K2 Campaign 9 (K2C9) was the first space-based microlensing parallax survey capable of measuring microlensing parallaxes of free-floating planet candidate microlensing events. Simultaneous to K2C9 observations we conducted the K2C9 Canada-France-Hawaii Telescope Multi-Color Microlensing Survey (K2C9-CFHT MCMS) in order to measure the colors of microlensing source stars to improve the accuracy of K2C9's parallax measurements. We describe the difference imaging photometry analysis of the K2C9-CFHT MCMS observations, and present the project's first data release. This includes instrumental difference flux light curves in up to three filters (g, r, and i) of 217 microlensing events identified by other microlensing surveys, reference image photometry of more than 30 million point sources calibrated to PanSTARRS data release 1 photometry with an absolute accuracy better than 0.02 mag . We derive accurate analytic transformations between the PanSTARRS bandpasses and the Kepler bandpass, as well as color-surface brightness relations in the PanSTARRS bandpasses. To demonstrate the use of our data set, we analyze ground-based and K2 data of a short timescale microlensing event, OGLE-2016-BLG-0795. We find the event has a timescale tE = 4.5 0.1 days and microlens parallax πE = 0.09 0.03 or 0.91 0.04, subject to the standard satellite parallax degeneracy. We argue that the smaller value of the parallax is more likely, which implies that the lens is likely a stellar-mass object in the Galactic bulge as opposed to a super-Jupiter mass object in the Galactic disk.